Feasibility of multiple breath washout measurements in infants with bronchiolitis: A pilot study. Issue 6 (21st February 2017) - Stafler, Patrick; Weinreb, Sigal; Mussaffi, Huda; Mei‐Zahav, Meir; Prais, Dario; Steuer, Guy; Bar‐On, Ophir; Hoshen, Moshe; Blau, Hannah
Abstract: BACKGROUND: Lung clearance index (LCI) reflects ventilation inhomogeneity and is raised in obstructive airway disease. Feasibility of multiple breath washout (MBW) measurement during acute lung disease in infants is unknown. As a further measure of disease, exhaled nitric oxide (eNO) may paradoxically decrease in acute bronchiolitis. We hypothesized that MBW measurements were attainable in infants with bronchiolitis and that LCI was raised and eNO reduced, compared to normal controls. METHODS: Infants with acute bronchiolitis were tested with sulfur hexafluoride (SF6 ) MBW during hospitalization and compared to controls. Tidal breathing and eNO parameters were obtained. Measurements were performed during natural sleep. RESULTS: Twenty‐nine infants with bronchiolitis aged 3.7 ± 2.3 months (mean ± SD) and 23 controls aged 4.2 ± 2.5 months ( P = 0.07) were evaluated. Fifteen of 29 (52%) infants with bronchiolitis and 19/23 (83%) controls achieved ≥2 valid MBW measurements. Reasons for test failure included waking up during facemask application and an irregular respiratory pattern. LCI was 8.4 ± 0.8 in the study group and 7.3 ± 0.7 in controls ( P < 0.001). ENO was 2.3 ± 2.7 ppb in the study group and 7.9 ± 6.9 ppb in controls ( P = 0.004). CONCLUSION: MBW measurements during natural sleep are feasible but technically challenging in infants with acute bronchiolitis. LCI is raised compared to healthy controls. Larger trials, possibly using sedation protocols and shortened washout periods, are required to corroborate these findings. LCI can potentially serve as an objective indicator of severity and could be considered as a biomarker for future interventional trials.